Day 2 Wed, December 07, 2016 2016
DOI: 10.2118/184146-ms
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Oil - Produced Water Polishing with Compact Flotation Technology

Abstract: For light and medium crude oil produced waters, the compact flotation unit (CFU) technology has been widely used as the final cleaning step in the process during the last 10 years, especially in Europe. In general, more traditional methods such as induced gas flotation (IGF) and dissolved gas flotation (DGF) are more commonly applied on heavy crude oil-produced waters. The CFU technology has been preferred over the more traditional technologies due to substantially reduced weight and footprint combined with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The retention time is typically less than 1 min. 31 The first CFU was introduced to the oil and gas industry at the NCS in 2001. 32 Today, the method has become well-proven and is used worldwide.…”
Section: Induced Gas Flotation (Igf)mentioning
confidence: 99%
See 1 more Smart Citation
“…The retention time is typically less than 1 min. 31 The first CFU was introduced to the oil and gas industry at the NCS in 2001. 32 Today, the method has become well-proven and is used worldwide.…”
Section: Induced Gas Flotation (Igf)mentioning
confidence: 99%
“…Vertical vessels are usually preferred, because they require less space and are less affected by wave motion. The retention time is typically less than 1 min . The first CFU was introduced to the oil and gas industry at the NCS in 2001 .…”
Section: Current Status Of Gas Flotation For Pw Treatmentmentioning
confidence: 99%
“…Different factors and conditions that can influence its efficiency at ambient conditions (e.g., salinity, surfactants, pH etc.) have been reported. , …”
Section: Introductionmentioning
confidence: 99%
“…Asdahl et al 25 examined the applicability and effectiveness of using CFU technology in heavy crude oil PW treatment. They observed that for a given oil, high oil removal efficiency was favored by larger oil droplets.…”
Section: Introductionmentioning
confidence: 99%